¿Qué es la salud y qué saberes se ponen en juego en los Bachilleratos Populares de Argentina? - Garelli, Fernando; Mengascini, Adriana Susana; Cordero, Silvina; Cucalón, Pilar; Dumrauf, Ana Gabriela (2017)
The Bachilleratos Populares (BP) are popular secondary schools for young and adults referenced in Latin American Popular Education, which emerged in Argentina in 2004. In this article, we present an initial study of Health Education in these experiences. We conducted interviews with teachers from 9 different BPs and focused our analysis on the ontological and epistemological dimensions of health. In the first one, health was considered as a field of intervention (seeking individual and/or collective transformations) from a multidimensional perspective, of rights and gender. In the epistemological dimension, we infer a supradisciplinary approach, recognizing various sources: academic knowledge (approached from a critical, denaturalizing perspective), popular knowledge and social movements. In this way, the bid found in these experiences of making a synthesis between Popular Education and Health Education in a school context, represents a contribution to the educational field, with dissident answers regarding hegemonic rationality and institutions.
Os Bachilleratos Populares (BP) sao escolas populares de ensino médio para jovens e adultos auto-gestivas e referenciadas na Educaçao Popular Latinoamericana, surgidas na Argentina em 2004. Neste artigo, apresentamos um estudo inicial da Educaçao em Saúde nestas experiências. Realizamos entrevistas com professores/as de 9 BPs e focalizamos nosso análise nas dimensoes ontológicas e epistemológicas da saúde. Na primeira delas, a saúde foi considerada como um campo de intervençao (buscando transformaçoes individuais e/ou colectivas) a partir de uma perspectiva multidimensional, de direito e de gênero. Na dimensao epistemológica, inferimos uma abordagem supradisciplinar, reconhecendo várias fontes: conhecimento acadêmico (abordado a partir de uma perspectiva crítica, de desnaturalizaçao), conhecimento popular e os movimentos sociais. Desta forma, a aposta encontrada nestas experiências de fazer uma síntese entre Educaçao Popular e Educaçao em Saúde no contexto escolar, representa uma contribuiçao para o campo educacional, com respostas dissidentes com respeito à racionalidade e instituiçionalidade hegemônicas.^lpt
Keywords: Bachilleratos populares; Health education; Popular education; Bachilleratos populares^lpt; Educaçao em saúde; Educaçao popular